Designers' guide to Eurocode 8 design of bridges for earthquake resistance : EN 1998-2 - Kolias, Basil (Eurocode designers' guide series, 2012)
Designers' Guide to Eurocode 8: Design of bridges for earthquake resistance covers Part 2 Bridges of EN 1998 Design of structures for earthquake resistance which is the standard for use in the seismic design of bridges in which horizontal seismic actions are mainly resisted through bending of the piers or at the abutments, and the seismic design of cable-stayed and arched bridges. The new addition to the bestselling Designers' Guides series was written by three world renowned authorities on the subject, who were instrumental in drafting the original code. Containing worked examples throughout, this book is the only guide which deals specifically with EN 1998-2.